ENVIRONMENTAL HEALTH CHALLENGES - S.GN. EZE, EZE (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2015)
The topic of this write-up is "Environmental Health Challenges". The importance of environmental health cannot be over-emphasized. No nation can achieve high level of health without good environmental condition. In this write up, efforts were made to examine the concept and components of environmental health, environmental health challenges and the way forward.